Study of the impact of bottleneck profiles on cork stopper behaviour using non-destructive techniques - Pereira, André Rosa Henriques (2023)
This thesis investigates the impact of bottleneck profiles on cork stopper behavior and performance using non-destructive techniques. Two novel thermal camera-based approaches were developed to assess the diameter recovery rate after extraction and measure absorption along the cork profile. The experimental findings demonstrate that the diameter recovery rate is influenced by the type of bottleneck profile, while the type of cork has a lesser impact. Furthermore, it is observed that the lower half of the cork exhibits a higher diameter recovery rate. Regarding absorption, the results indicate that it is primarily influenced by the type of cork stopper rather than the chosen bottleneck shape, with natural corks displaying significantly higher absorption values. The analysis and acquisition involved the utilization of computer vision and programing software.